Kemampuan Siswa dalam Menyelesaikan Soal-soal Fisika Materi Gerak Lurus Berubah Beraturan - Ikbal; Muhammad Ali; Muhammad Jarnawi (Jurnal Kreatif Online, 2021)
Problem solving cannot be separated from learning Physics. This study aims to determine the ability of physics problems solving on non-uniform linear motion topic. This research was descriptive research. The research subjects were 10 students of class X IPA 2. Data obtained through student ability tests and interviews. The results showed that the students' ability to solve physics problems on non-uniform linear motion topic was included in the good category with an average value of 75.62 with the percentage of each indicator, which were 77.50% the ability to translate sentence questions into symbols, 75.00% ability to understand the formula that will be used to answer the questions, 71.67% ability to use formulas to answer questions and 78.33% ability to use units correctly.